158 A Systematic Review of Pharnmacokinetics (Pk) of Dobutamine for use in Neonates and Children. (October 2012) - Shah, GS; Crook, D; Rojas-Anaya, H; Rabe, H
Abstract : Background: Dobutamine has been used off-label in newborns and children for treating haemodynamic insufficiency for over 20 years. As preparation for a large randomised study to achieve Paediatric Use Marketing Authorisation for dobutamine in newborns we performed a structured literature review of PK data. Methods: Structured searches were conducted using the electronic databases Medline and Embase. Search terms included dobutamine, infant, newborn, paediatric/pediatric, prematurity, child, infant, low birth weight infant, preschool child, school child, adolescent, pharmacokinetics, clinical pharmacology. Data was extracted based on pre-defined criteria decided by the team. Main results: Six of eleven papers emerging from this search met our inclusion criteria. These reported dobutamine PK data in a combined total of 70 children (age range 0 days-22 years, 13 newborns, 27–42 weeks gestation), with infusion rates ranging from 0.5–20 µg/kg/min. Five papers found that the infusion rate was positively correlated to plasma dobutamine concentration. Dobutamine clearance rates showed great variability between individuals (range 35.1–482.2 mL/kg/min). Four papers found that clearance did not vary with infusion rate, suggesting first order kinetics, although one paper (n=12) showed a significantly negative relationship (p<0.001) of dobutamine clearance to steady-state plasma concentration (dobutamine dosage 2–15 µg/kg/min). Conclusions: The current dobutamine PK data is difficult to interpret due to inhomogeneity and variability of patients' age and conditions, dobutamine dosages and study designs. High quality prospective PK data -especially in newborns- is urgently required prior to our large randomised study.